THE EFFECTIVENESS OF USING PECHA KUCHA TECHNIQUE TO PROMOTE STUDENTS’ SPEAKING SKILL - Eva Faliyanti; Devi May Ratih (Intensive Journal, 2021)
The aimed of this research is to test the effectiveness of using Pecha Kucha Technique in students’ speaking performance at fourth semester of English Department in Muhammadiyah University of Metro. Pecha Kucha is a presentation form of 20 pictures for 20 seconds and it is also called 20x20 presentations.The entire presentation always lasts for exactly 6 minutes and 40 seconds. The research method used in this research is an experimental research. The subjects of this research are the students at fourth semester of English Department in Muhammadiyah University of Metro academic year 2020. There are 21 students of control group and 21 students of experimental group. The research instrument used to collect the data in this research is an oral test. From the two classes, the experimental and control group, the measurement shows that increasing line of the speaking ability of the experimental group is higher than the control group. The result of pre-test score shows that the average score of the experimental group and the control group are 52.38 and 56.19. From the score of both groups, the result shows that the control group is better than experimental group. Then, the result of the post test of the experimental group is higher than control group; the average scores are 70,71 for experimental group and 62.38 for control group. It can be concluded that there is significant influence of using Pecha Kucha Technique in students’ speaking skill.